Effect of Self-Selected Individual Music Therapy (SeLIMuT) on Stress and Depression Levels in Patients with Diabetic Foot Ulcers - Haerianti, Masyita; Wabulan, Irfan (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Type 2 diabetes mellitus (T2DM) is a metabolic disease that causes complications such as diabetic foot ulcers, with the majority of patients with ulcers experiencing stress and depression. One therapy that can be administered to address stress and depression is music therapy through self-selected individual music therapy (SeLIMuT), which aims to address the side effects of stress and depression, such as enhanced wound healing and improved quality of life. This study aims to determine the effect of individually selected music therapy (SeLIMuT) on stress and depression levels in patients with type 2 diabetes mellitus and diabetic foot ulcers at the Ikram Wound Care Center in Majene District. The study employed a quasi-experimental design with pre-test and post-test design. The sample consisted of 17 patients with type 2 diabetes mellitus and diabetic foot ulcers. The independent variable was the effect of SeLIMuT, and the dependent variables were stress and depression. The instruments used in this study were the Depression Anxiety Stress Scale 42 (DASS-42) questionnaire, an MP3 player, and headphones. Data analysis was conducted using the Wilcoxon test, which showed that SeLIMuT was able to reduce stress levels (p=0.000, p0.05) and depression (p=0.000, p0.05) in patients with type 2 diabetes mellitus and diabetic foot ulcers.